2023
DOI: 10.1186/s12893-023-02192-3
|View full text |Cite
|
Sign up to set email alerts
|

A simple and effective technique for laparoscopic gastrorrhaphy: modified Graham’s patch with barbed suture

Ta-Chun Chou,
Chun-Hui Lee,
Ruey-Shyang Soong
et al.

Abstract: Introduction Peptic ulcers are caused by unbalanced acid production, and proton pump inhibitors (PPIs) in recent decades have helped to treat peptic ulcers effectively. Meanwhile, the incidence of perforated peptic ulcer (PPU) persists and has a high mortality rate if there is no adequate management. Primary closure with a modified Graham’s patch was well performed in early detected PPU with a small size < 2 cm. A laparoscopic approach for PPU was prescribed for decades with proven feasibili… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 15 publications
0
4
1
Order By: Relevance
“…In contrast with previous research, our study showed comparable operative time using knotless barbed sutures compared to conventional interrupted stitches [ 18 , 19 , 20 ]. One possible explanation could be the laparoscopic skill of the surgeons.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In contrast with previous research, our study showed comparable operative time using knotless barbed sutures compared to conventional interrupted stitches [ 18 , 19 , 20 ]. One possible explanation could be the laparoscopic skill of the surgeons.…”
Section: Discussioncontrasting
confidence: 99%
“…The successful implementation of laparoscopic PPU repair is also owed to the development of new suture materials, notably knotless barbed sutures [ 20 ]. Despite some drawbacks like higher costs and irreversibility, knotless barbed sutures have gained acceptance in general surgery [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations